Community-aquired pneumonia associated with coronavirus disease (COVID-19): determination of pathological process progression predictors by clinical and hemocoagulation parameters - Pertseva , T.O.; Bielosludtseva , K.O.; Konopkina, L.I.; Krykhtina , M.A.; Myronenko , O.V.; Botvinikova , L.A.; Moiseienko , O.F. (Medicni Perspektivi, 2022)
The search for clinical and laboratory markers of COVID-19-associated CAP progression is an urgent problem of today. The aim of our study was to determine the risk factors for the burden of the pathological process by establishing the diagnostic and prognostic significance of clinical and hemocoagulation parameters in the hospital stage of management of patients with CAP on the background of coronavirus disease (COVID-19). The study included 53 individuals of the main group. All patients were examined twice: on the first day of hospitalization (visit 1) and in the dynamics (7-10 days after hospitalization (visit 2)). In 30 (83.3%) patients of subgroup 1, despite adequate treatment, there was an increase in breathing rate and a decrease in saturation to severe (less than 92%) or critical (less than 85%) levels (in 28 and 2 cases respectively). In subgroup 2, the progression of respiratory failure to a critical level was observed in 5 of 12 (41.7%) patients. Conclusions: at the stage of hospitalization of patients with COVID-19-associated CAP the most sensitive clinical predictor of aggravation of the patient’s condition is tachypnea of 20 or more; laboratory – the level of D-dimer 200 ng/ml, which increases the risk of progression of the pathological process by 16 times.